(untitled) (Tanzania Medical Journal, 2025)
Background One of the major reasons for orthopedic consultation during the first decade of life is flatfoot. Flat-footedness may be classified into two main types namely pathological or physiological. The main objective of this study was to assess the occurrence of flatfoot in primary school children in terms of prevalence and anatomical presentation. Materials and Methods This study carried out at a primary school in Temeke district in Dar es Salaam. We recruited 159 children between the ages of 6 and 10 years. Any child with a history of foot pathology which may interfere with foot readings e.g. foot ulcers, fractures, sores etc. were excluded from this study. The method proposed to determine flat footedness in this study is the Staheli Plantar Arch Index method. Results Only 9.4% (n=15) of the participants examined had flatfoot. Of the 15 participants who had flat foot 46.7% (n=7) had flatfoot bilaterally. The plantar arch index of the right foot of the children examined ranged between 0.39 and 1.65 (mean of 0.87 ± 0.23). The plantar arch index of the left foot of the children examined ranged between 0.26 and 1.91 (mean of 0.88 ± 0.28). Conclusion Flatfoot is a relatively common orthopedic condition in childhood with a prevalence of 9.4% in this study.